Christian European Travelers' Views on Nawab Bahawal Khan III, the Muslim Ruler of Bahawalpur State (Al-Qamar, 2024)
This article delves into the unique perspective of Christian European travelers on Nawab Bahawal Khan III, offering direct insights into their views on the Muslim ruler of Bahawalpur State. Other sources fail to provide a comprehensive portrayal of Nawab Bahawal Khan III's personality. These travelers encountered the nawab at various times and documented their observations about his personality, court, habits, and way of speaking in their travel accounts. Despite the predominant motive of British travelers being missionary work during that era, they surprisingly held favorable opinions about the nawab. While these travelers did forge political connections, their underlying agenda also included the propagation of Christianity. Hence, it is intriguing to note their positive opinions about a Muslim local ruler along with his generosity and delightful hospitality.
Keywords: Christian; European Travelers; Nawab Bahawal Khan III; Bahawalpur